Effectiveness of the PSI BLAST algorithm in dependence on scanning word size - Margelevičius, Mindaugas; Timinskas, Albertas (Lietuvos matematikos rinkinys, 2003)
The alignment searching algorithms for biomolecular sequences PSI-BLAST are reviewed in the article. We asses the feasibility to modify NCBI (National Center for Biotechnology Information) PSI-BLAST implementation. We modify the implementation of the iterative algorithm by increasing scanning word size. We also accomplish statistical analysis for each enzyme of the cytosine-5 methyltransferase family after we apply alignment searching for the biologically related protein sequences.